Myocardial T2‐mapping and velocity mapping: Changes in regional left ventricular structure and function after heart transplantation. Issue 2 (24th September 2012) - Markl, Michael; Rustogi, Rahul; Galizia, Mauricio; Goyal, Amita; Collins, Jeremy; Usman, Asad; Jung, Bernd; Foell, Daniela; Carr, James
<x xml:space="preserve">Abstract</x> Monitoring post cardiac transplant (TX) status relies on frequent invasive techniques such as endomyocardial biopsies and right heart cardiac catheterization. The aim of this study was to noninvasively evaluate regional myocardial structure, function, and dyssynchrony in TX patients. Myocardial T2‐mapping and myocardial velocity mapping of the left ventricle (basal, midventricular, and apical short‐axis locations) was applied in 10 patients after cardiac transplantation (49 ± 13years, n = 2 with signs of mild rejection, time between TX and MRI = 1–64 months) and compared to healthy controls (n = 20 for myocardial velocity mapping and n = 14 for T2). Segmental analysis based on the 16‐segment American Heart Association model revealed increased T2 (P = 0.0003) and significant (P < 0.0001) reductions in systolic and diastolic radial and long‐axis peak myocardial velocities in TX patients without signs of rejection compared to controls. Multiple comparisons of individual left ventricular segments demonstrated reductions of long‐axis peak velocities in 50% of segments (P < 0.001) while segmental T2 values were not significantly different. Systolic radial as well as diastolic radial and long‐axis dyssynchrony were significantly (P < 0.04) increased in TX patients indicating less coordinated contraction, expansion, and lengthening. Correlation analysis revealed moderate but significant (P < 0.010) inverse relationships between myocardial T2 and long‐axis peak velocities suggesting a structure–function relationship between altered T2 and myocardial function. Magn Reson Med 70:517–526, 2013. © 2012 Wiley Periodicals, Inc.